“Re-educating” Tumor Associated Macrophages as a Novel Immunotherapy Strategy for Neuroblastoma - Liu, Kevin X.; Joshi, Shweta (Frontiers in Immunology, 2020)
Neuroblastoma is the most common extracranial pediatric tumor and often presents with metastatic disease, and patients with high-risk neuroblastoma have survival rates of approximately 50%. Neuroblastoma tumorigenesis is associated with the infiltration of various types of immune cells, including myeloid derived suppressor cells, tumor associated macrophages (TAMs), and regulatory T cells, which foster tumor growth and harbor immunosuppressive functions. In particular, TAMs predict poor clinical outcomes in neuroblastoma, and among these immune cells, TAMs with an M2 phenotype comprise an immune cell population that promotes tumor metastasis, contributes to immunosuppression, and leads to failure of radiation or checkpoint inhibitor therapy. This review article summarizes the role of macrophages in tumor angiogenesis, metastasis, and immunosuppression in neuroblastoma and discusses the recent advances in “macrophage-targeting strategies” in neuroblastoma with a focus on three aspects: 1) inhibition of macrophage recruitment, 2) targeting macrophage survival, and 3) reprogramming of macrophages into an immunostimulatory phenotype.